International Evidence of COVID-19 and Stock Market Returns: An Event Study Analysis - Bash, Ahmad (International Journal of Economics and Financial Issues, 2020)
We study the effect of the first registered case of COVID-19 on stock market returns using event study analysis. Mean-adjusted returns and market model methods are used to estimate cumulative abnormal returns for 30 countries. The results show that stock market returns experience a downwards trend as well as significant negative returns following the COVID-19 outbreak. Keywords: COVID-19, event study, index returns; pandemics JEL Classification: G14 DOI: https://doi.org/10.32479/ijefi.9941